Analisis Wacana Kohesi Pada Teks Debat Calon Presiden Prabowo Subianto Tahun 2024 - Indah Afrianti; Rusdin Rusdin; Nur Wahyuni; Wulandari Wulandari (Journal on Education, 2024)
The research on "Text Cohesion Analysis of Prabowo's Speeches in the Election of Presidential Candidates and Vice Presidential Candidates in 2024" examines the forms of lexical cohesion and grammatical cohesion in the context of the 2024 Prabowo Subianto presidential candidate debate text. The descriptive qualitative methodology was used to analyse the data. The data source for this research is the text recording of the 2024 presidential candidate debate sourced from National TV broadcasts and online news outlets on Narasi.tv. Data was collected for this research through the use of the observational method, accompanied by note-taking techniques. The discourse theory-based agih method was utilized for the data analysis. The findings of this research revealed the existence of lexical cohesion and grammatical cohesion in the texts under examination. The grammatical cohesion observed comprises personal referential elements, including singular and plural first person pronouns, demonstrative references in the past tense, substitutions and conjunctions. In contrast, lexical cohesion is observed in only a few instances, such as repetition and synonymy. This article aims to provide a deeper understanding of discourse, particularly with regard to lexical cohesion and grammatical cohesion.